Special based isolation system for low-rise RC building - Hamid, N. H.; Azmi, I. F.; Tiong, P. L. Y.; Haryati, Awang (IOP Publishing Ltd., 2019)
In the past decade, there were a lot of seismic activities around the world that cause low rise reinforced concrete suffered severe damage and total collapse. A special based isolation system can be equipped to the low rise building to prevent it from damaged and collapse by improving the period, stiffness and damping of the structures. The based isolation system can increase the natural period of a rigid structure under first mode shape by applying low stiffness rubber isolators. These method can provide a better structural behaviour of low rise RC building as compared to moderate or high stiffness rubber isolators. Furthermore, the special based isolation system with maximum damping of 15% for 4 storey and 6 storey RC building. However, the value of optimum damping depends upon the characteristics of ground motions and frequencies of the earthquakes.